Assessment of the influence of horizontal diaphragms on the seismic performance of vernacular buildings - Ortega, Javier (2019)
The awareness and preservation of the vernacular heritage and traditional construction techniques and materials is crucial as a key element of cultural identity. However, vernacular architecture located in earthquake prone areas can show a particularly poor seismic performance because of inadequate construction practices resulting from economic restraints and lack of resources. The horizontal diaphragms are one of the key aspects influencing the seismic behavior of buildings because of their major role transmitting the seismic actions to the vertical resisting elements of the structure. This paper presents a numerical parametric study adopted to understand the seismic behavior and resisting mechanisms of vernacular buildings according to the type of horizontal diaphragm considered. Detailed finite element modeling and nonlinear static (pushover) analyses were used to perform the thorough parametric study aimed at the evaluation and quantification of the influence of the type of diaphragm in the seismic behavior of vernacular buildings. The reference models used for this study simulate representative rammed earth and stone masonry vernacular buildings commonly found in the South of Portugal. Therefore, this paper also contributes for a better insight of the structural behavior of vernacular earthen and stone masonry typologies under seismic loading.